2022
DOI: 10.3390/ani12233302
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Fatty Acids and Localization of SREBP1 and ELOVL2 Genes in Cauda Epididymides of Hu Sheep with Different Fertility

Abstract: The epididymis is an organ that transports, matures and stores sperm, and has functions such as secretion and absorption. Polyunsaturated fatty acid (PUFA) compositions in sperm membrane were changed during the process of epididymis maturation and influence the male fertility. This study aimed to investigate differences in crude fat and fatty acid content in cauda epididymis between high and low fertility of Hu sheep. One hundred and seventy-nine Hu ram lambs were fed from 56 days to 6 months under the same en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Although studies on its function in female reproduction are lacking, several studies have demonstrated its fundamental role in male fertility in mammals (Zadravec et al, 2011;Olia Bagheri et al, 2021;Castellini et al, 2022;Liu et al, 2022). Regulation of pH also plays a role in sperm survival and activity in the UVJ of birds (Holm et al, 1996;Holm and Wishart, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on its function in female reproduction are lacking, several studies have demonstrated its fundamental role in male fertility in mammals (Zadravec et al, 2011;Olia Bagheri et al, 2021;Castellini et al, 2022;Liu et al, 2022). Regulation of pH also plays a role in sperm survival and activity in the UVJ of birds (Holm et al, 1996;Holm and Wishart, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the productivity of Tan sheep meat, the Tan sheep Breeding Project Team introduced excellent Hu sheep for crossbreeding, in order to improve the production performance of Tan sheep without affecting the quality and flavor of Tan sheep. The Hu sheep is extensively reared for its high litter size (5,6), and its muscle growth rate is faster than that of Tan sheep (7)(8)(9). Their hybrid offspring also grew faster than Tan sheep (data not published).…”
Section: Introductionmentioning
confidence: 99%